1997
DOI: 10.1021/ac970470k
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Free Radical Ionization Energies by the Kinetic Method and the Relationship between the Kinetic Method and the Hammett Equation

Abstract: Substituted 1,2-diphenylethanes undergo competitive dissociations upon electron ionization (EI) to generate substituted benzyl cation and benzyl radical pairs. Application of the kinetic method to the previous reported EI mass spectra of these covalently bound precursor ions (data are taken from McLafferty et al. J. Am. Chem. Soc. 1970, 92, 6867)) is used to estimate the ionization energies of substituted benzyl free radicals. A correlation is observed between the Hammett σ constant of the substituents and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For example, Wenthold and Squires estimated Δ H acid of halogen‐substituted aromatic compounds by hydroxide‐induced cleavage and found the effective temperature of the siliconate ion to be of the order of 4400 K 45. In this laboratory, we found effective temperatures of 3073 ± 500 and 2527 ± 150 K for the EI dissociation of substituted 1,2‐diphenylethanes at 70 and 15 eV, respectively 41. In addition, Meurer et al 42 observed an effective temperature of 1705 K for the dissociation of ionized α‐diketones under mild conditions (CID at 5 eV collision energy).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…For example, Wenthold and Squires estimated Δ H acid of halogen‐substituted aromatic compounds by hydroxide‐induced cleavage and found the effective temperature of the siliconate ion to be of the order of 4400 K 45. In this laboratory, we found effective temperatures of 3073 ± 500 and 2527 ± 150 K for the EI dissociation of substituted 1,2‐diphenylethanes at 70 and 15 eV, respectively 41. In addition, Meurer et al 42 observed an effective temperature of 1705 K for the dissociation of ionized α‐diketones under mild conditions (CID at 5 eV collision energy).…”
Section: Resultsmentioning
confidence: 59%
“…Similar results were obtained by McLafferty et al ,1 as already mentioned in the Introduction. It is important to state that the Hammett equation is closely related to the kinetic method approach, as demonstrated previously 41…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The reference value of IE a (CF) provides an internal standard, which is lacking in the absolute appearance energy measurements and which is expected to compensate for most of the systematic error. Formally, this is similar to the mass spectrometric “kinetic method” of measuring the relative energetics of competing ion−molecule reactions. , In that context, it would be interesting to see the data of ref plotted and analyzed as a branching ratio. Another alternative analysis method would be in terms of competing kinetic processes, as described recently for the collision-induced dissociation of multiply ligated ions …”
Section: Critique Of the Above Analysismentioning
confidence: 99%
“…Cooks' kinetic method typically uses observed abundance ratios of ions formed competitively from a common cluster ion to find their thermochemical properties when their structures are known 46, 47. There are reports of determination of relative ionization energies ( I ) by this method,48–51 and the following description of the method is derived from these. We shall take a different approach, however, using such observed abundance ratios (Table 3) with theoretical I to find the best fit among plausible isomeric structures and thus fragmentation mechanisms 52…”
Section: Resultsmentioning
confidence: 99%